Bicalutamide (Casodex®®) in the treatment of prostate cancer. Issue 1 (1st February 2004) - Fradet, Yves
Prostate cancer is an important healthcare issue in men worldwide. With the advent of prostate-specific antigen screening and improved diagnostic techniques, prostate cancer is now being diagnosed in younger men and at earlier disease stages. As a result, patients often live with their disease for many years after diagnosis. This shift in the patient profile has focused attention to the impact of treatment on quality of life. Medical/surgical castration has traditionally been the mainstay of hormonal therapy but is associated with side effects including loss of libido and impotence. Nonsteroidal antiandrogens such as bicalutamide (Casodex ®® ) offer an effective alternative to castration with potential quality-of-life benefits. This paper reviews the evidence concerning the use of bicalutamide at all stages of the disease.